Принципи геометричної кореляції при побудові моделей багатофакторних ситуацій і процесів - Адоньєв, Євген Олександрович; Верещага, Віктор Михайлович (НТУ "ХПІ", 2017)
Із застосуванням геометричної формалізації, розробленої на основі точкового БН-числення, доведено необхідність і введено новий математичний термін – "геометрична кореляція". З використанням геометричної кореляції запропоновано алгоритм розв'язання задач багатовимірного евклідового випуклого простору Еn через розв'язання відповідної кількості одно-, двох-, трьохвимірних задач з подальшою суперпозицією отриманих розв'язків. Надано класифікацію принципів геометричної кореляції, наведено приклад алгоритму з використанням одного з принципів побудови моделі багатофакторної ситуації.

In modeling processes in the field of energy saving, the problem of combining a large number of physically heterogeneous factors often arises. Existing methods of mathematical modeling, as a rule, require the establishment of a correlation between the input values of the future model, and then, based on the correlation results, a model is constructed. It always puts in the model certain limitations on the number of factors that can be included in the model, in the size of the matrices, and so on. In addition, the need to integrate physically diverse factors further complicates modeling with traditional methods. In our opinion, these drawbacks are deprived of compositional methods of geometric modeling, whose geometrical formalization takes place with the help of algebraic methods of the point BN-calculus (Balyuby-Nidische calculus), because of the representation in the analytical form of correlation geometric shapes by creating the corresponding geometric aggregates. In the article, using the geometric formalization de-veloped on the basis of point BN-calculus, the necessity and a new mathematical term - "geometric correlation" - was proved. Using geometric correlation, an algorithm for solving problems of a multidimensional Euclidean convex space Еn through a solution of the corresponding number of one-, two-, and three-dimensional problems with further superposition of the solutions obtained is proposed. A classification of the principles of geometric correlation is given, an example of an algorithm is given with the use of one of the principles for constructing a model of a multifactorial situation.
Principles of geometric correlation in the construction of models of multifactorial situations and processes
Keywords: геометрична формалізація; геометрична кореляція; багатофакторна ситуація; geometric formalization; geometric correlation; multifactorial situation